The Islamist version of utopia: The politics of redesigning space - Sahin, Seval; Buyukarman, Didem Ardali (INST WORLD LITERATURE, SLOVAK ACAD SCIENCES, 2021)
This article examines utopian novels by two Islamist Turkish writers: Ali Nar's The Space Farmers (Uzay Ciftcileri, 1988) and Ayse Sasa's The Novel of the Monkeys (Sebek Romani, 2004), which were celebrated among Islamist circles upon their publication. In these two novels, the corruption and pollution of place/space is blamed upon the Christian Western civilization. They depict how the desired regime change will begin in Turkey and expand towards Europe and then to the rest of the world, through the portrayal of oppositional places as utopian/dystopian spaces. The article discusses the ways in which space/place is ideologically redesigned in the Islamist imagination as a political symbol and analyze how these popular Islamist writers present the world and the space for their utopian vision of Islamist supremacy.
Keywords: Islam; Utopia; Place/Space; Ali Nar; Ayse Sasa; Western civilization; Literature